Understanding the microbiome in autologous haemopoietic stem cell transplant for multiple sclerosis - Yin, Jun; Kaakoush, Nadeem O.; Massey, Jennifer; Danta, Mark (Frontiers in Immunology, 2025)
BackgroundMS is a chronic inflammatory and degenerative disease of the central nervous system (CNS) resulting in neurological deficits associated with physical and/or cognitive disability. The gut microbiome can interact with the CNS and immune system through various molecular pathways and has been previously implicated in MS. Autologous Haematopoietic Stem Cell Transplant (AHSCT) in MS arrests inflammatory disease and has evidence of long-term therapeutic benefit. To date, no study has explored the effect of AHSCT on the gut microbiome in people with MS.MethodThe microbiome of people with MS (pwMS) undergoing AHSCT was compared with pwMS on Natalizumab (NTZ). Longitudinal microbiome analysis was also conducted within the AHSCT cohort at two timepoints. Amplicon sequencing of the 16S ribosomal RNA V3–4 region (Illumina MiSeq) was used to evaluate alpha and beta diversity, oral-stool microbiota distances, and relative taxa abundances on both oral and stool microbiota.ResultsThe pre-transplant, baseline samples from the AHSCT cohort (n=8) was compared to the Natalizumab group (n=22). The AHSCT cohort had lower oral species richness compared to the NTZ cohort (p=0.026). There was a significant difference in oral beta diversity between the two cohorts (p=0.043). The oral taxa analysis of AHSCT subjects showed increased relative abundances of Porphyromonas and decreased Veillonella.ConclusionThis pilot study identified specific microbiome changes, particularly in the oral alpha diversity and abundance of specific bacteria which may reflect treatment status or disease activity in MS.